Serological differentiation of human small fluke infections using Opisthorchis viverrini and Haplorchis taichui antigens - Ditrich, O; Kopacek, P; Giboda, M; Gutvirth, J; Scholz, T (The Southeast Asian journal of tropical medicine and public health, 1991)
Sera from 642 inhabitants of Vientiane Province (Laos) were examined by enzyme-linked immunosorbent assay (ELISA) using cytoplasmic and membranous antigens prepared from adult worms. Worms of Opisthorchis viverrini originated from liver of dissected cats, Haplorchis taichui were obtained from a stool specimen of a Laotian patient after praziquantel treatment. The sera were divided into five groups according to the intensity of infection expressed as egg count per gram of patients stool (EPG). Correlation between intensity of infection and the level of antibodies in serum was recorded. Reactions obtained using the cytoplasmic antigens were more sensitive and more specific compared to those with membranous antigens. Cross-reactions between antigens of both helminth species were found. Highly positive sera were examined using electroimmunotransfer blots (EITB) with cytoplasmic antigens of both species, which enabled the species differentiation. Antigens of both species yielded several shared fractions; however, differences between them were found: homologous sera reacted specifically with O. viverrini antigen in the area of 70 kDa and with H. taichui antigen in the area of 10 kDa. Thirty-one of 122 tested sera had specific antibodies against O. viverrini, 77 sera against H. taichui and 14 sera against both species. The results confirmed our assumption about predominant occurrence of heterophyid flukes in the human population living in studied area, compared with the occurrence of opisthorchid flukes. Hence, serology seems to be helpful tool for correct diagnosis of small fluke infections.
Keywords: Antibodies, Helminth; antigeny povrchové; Animals; Enzyme-Linked Immunosorbent Assay; infekce červy třídy Trematoda; Antigens, Helminth; Trematode Infections; lidé; protilátky helmintové; zkřížené reakce; Sensitivity and Specificity; senzitivita a specificita; Cross Reactions; Immunoblotting; antigeny helmintové; ELISA; Opisthorchis; Heterophyidae; imunoblotting; zvířata; Antigens, Surface; Humans